Estratégia de crescimento de novas verticais de vendas no e-commerce - Massari, Murilo (2020)
The scenario of online sales is dynamic and is inserted in an environment of digital disruption, where there is more and more competition between companies, as well as the consumers are more connected and interacting with multiple contact channels with the retailer. For ecommerce to grow, be profitable, and achieve consumers needs and desires, involved in a nonlinear shopping journey and in an environment of digital disruption, it is necessary to adapt and invest in technology, in management of multidisciplinary teams, in new sales channels, in new markets and/or new verticals and products. Driving new sales verticals to grow in a disruptive environment is a challenge that will involve focusing on company core business and new adjacencies to the business, aligning with strategy and operation, through the integration between marketing and sales teams, and this can be understood by analyzing and reviewing the sales activities within the sales funnel steps. The purpose of the research is to analyze how the alignment of marketing and sales teams can be made to boost a new vertical, within a disruptive business. The researcher used a qualitative approach method, with a study case of an ecommerce player in Brazil’s sport and fashion market, through a documentary review of the company and semi-structured interviews with sales and marketing teams. The company’s core business, since its start up, is the sales of sneakers and sport shoes and, to boost a new vertical, apparel, the research indicated, first of all, that understand the specific characteristics or this vertical is necessary, which hinder the management of the business, such as constant innovation, with several collections during the year, the existence of an infinite number of suppliers, brands and types of products, and the lack of standardization of sizes and models. The results of the work indicated that, to boost the growth of the new vertical, it is necessary to: invest in branding actions of the virtual store, have exclusive teams for the vertical sales, implement an omnichannel strategy, invest in actions directed to the base company customers, improve the cataloging of products on the website, improve the virtual fitting room, improve and facilitate the exchange and returns products policy, enhance actions with scoring programs for the clients with business partners and actions for sales with the company’s own credit card.